2017
DOI: 10.1089/mdr.2016.0089
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Extended-Spectrum β-Lactamases Among Clinical Isolates ofKlebsiella pneumoniaein Gaza Strip, Palestine

Abstract: Sixteen broad-spectrum cephalosporin-resistant Klebsiella pneumoniae isolates were recovered between April and June 2013 from Palestinian hospitals, Gaza Strip. Genes encoding extended-spectrum beta-lactamases (ESBLs) and other resistance genes were characterized by polymerase chain reaction and sequencing. The following β-lactamase genes were detected: bla+ bla+ bla (six isolates), bla+ bla+ bla (two isolates), bla (two isolates), bla+ bla (one isolate), bla+ bla (one isolate), bla+ bla+ bla(one isolate), bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…This increase appears to be correlated with the clonal expansion of ST131 E. coli strains carrying the blaCTX-M-14 and blaCX-M-15 genes (Karfunkel et al, 2013). ESBL production by K. pneumoniae in clinical settings was reported, whereby CTX-M-15, CTX-M-14a, CTX-M-3, SHV-12, SHV-5, and SHV-33 were detected (Tayh et al, 2017). In Jordan, very few studies have addressed the prevalence of ESBL producers in clinical settings.…”
Section: Distribution Of Multi-drug Resistant Organisms In Humansmentioning
confidence: 99%
“…This increase appears to be correlated with the clonal expansion of ST131 E. coli strains carrying the blaCTX-M-14 and blaCX-M-15 genes (Karfunkel et al, 2013). ESBL production by K. pneumoniae in clinical settings was reported, whereby CTX-M-15, CTX-M-14a, CTX-M-3, SHV-12, SHV-5, and SHV-33 were detected (Tayh et al, 2017). In Jordan, very few studies have addressed the prevalence of ESBL producers in clinical settings.…”
Section: Distribution Of Multi-drug Resistant Organisms In Humansmentioning
confidence: 99%
“…Notably, we previously reported the pandrugresistant OXA-48-producing Proteus mirabilis and clonal spread of toxic shock syndrome toxin (TSST-1)-producing methicillin-resistant Staphylococcus aureus (MRSA) in the same area (16,17). In addition, ESBL-producing Escherichia coli and Klebsiella pneumoniae, NDM-2-producing Acinetobacter baumannii, and VIM-producing P. aeruginosa from Gaza have also been documented (18)(19)(20). Apparently, besides other challenges, Gaza is facing an antimicrobial resistance crisis as a result of the emergence of these highly multidrug-resistant organisms.…”
mentioning
confidence: 97%
“…We found ISEcp1 upstream of the bla CTX-M-15 gene in all strains. This insertion sequence is also able to provide promoter sequences enhancing the expression of the bla CTX-M gene (2 (30). The conjugation studies revealed the transfer of plasmids carrying bla CTX-M-15 in all isolates.…”
Section: Discussionmentioning
confidence: 97%